Situation Report: Czechoslovakia, 10 August 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Charter 77 Outlines Global Strategy for Peace Slovak Intellectuals Stand Up for Miklos Duray New Regulations on Czechoslovak-Polish Tourism Heath Care in Czechoslovakia Protest Songs